Induksi Ketahanan terhadap Penyakit Hawar Daun Bakteri pada Tanaman Padi di Lapangan Menggunakan Rizobakteri Indigenos - Andi Khaeruni; Abdul Rahim; Syair .; Adriani . (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2014)
ABSTRACTInduced resistance to bacterial leaf blight disease in rice field by indigenous rhizobacteria. Bacterial leaf blight is the most important disease on paddy at Southeast Sulawesi. Utilization of biological agents that induce plant resistance is an alternative tool to control bacterial leaf blight disease on paddy. The aim of the experiment was obtain rhizobacteria that were able to stimulate the growth of paddy plants as well induce plant resistance towards bacterial leaf blight in the field. All experiment units were arranged with a factorial design in a randomized complete block design. The first factor was the rhizobacteria isolates, consisting 4 treatments, i.e: without rhizobacteria (R0), isolate P11a (R1), isolate PKLK5 (IR2), and mixture P11a and PKLK5 (R3), the second factor is paddy varieties, (V1): IR64 variety, (V2): Cisantana variety. The pathogen was inoculated on leaf when 45 day after crop. Weekly observation of disease severity, vegetative plant growth (leaf and stem numbers), and yield were conducted. The results showed that the 10 isolates of rhizobacteria tested were able to induce plant resistance toward bacterial leaf blight, stimulated vegetative growth as well as increased yield of paddy plant. Rhizobacteria application could increase the resistance of paddy toward Xanthomonas oryzae pv. oryzae. The application rhizobacteria could increase the vegetative plant growth, application mixture P11a and PKLK5 isolates showed higher resistance than single application in terms of plant growth and yield, both IR64 and Cisantana varietes